VALUE ALIGNMENT BETWEEN EMPLOYEE AND COMPANY AT PT. XYZ (The Indonesian Journal of Business Administration, 2019)
PT XYZ is one of start-up company in Indonesia. It established in 2018. It focuses on the technology business. The company believes that its product would be the first innovation in the world. Initially, the product will be launched in April 2019, but due to obstacles in the production process, launching was postponed until Q1 2020. Currently, PT XYZ has 30 employees in May 2019. Based on people planning forecast, total employees next year will be around 100 people. Most of the employees are experienced and have expertise in technology competency. As a new company, PT XYZ commits building a positive organization that referring to humanism as an organizational approach. The company has 3 company values: Continuous Improvement, Respect Each Other, and Radical Knowledge. To help the company find out the root cause of the business issue until propose the solution, the researcher using interview and observation as research method. Interview not only conducted for the employees, but also with Board of Director (BOD) and Head of Human Capital (HC). On top of that, in the beginning of this study, the researcher analyze the issue by reviewing existing company’s data, such as, team performance monitoring and internal assessment result.  According to above approach, the researcher find out the main issue of this company is value incongruence between employee and company that impacted to the personal and team’s performance. Currently, PT XYZ has not designed yet the strategies or programs to help employees to align with company’s value. Following up this condition, the researcher focus to explore the actual behavior gap of employees that indicate value incongruence. Then, propose program solution that address those gaps. The researcher proposes 5 programs as business solution, such as, Coaching Program, Conducted Fun Collaboration, Establish Pilot Project: Outside-Office-Activities, Design Standard Operational of Problem Solving and Improvement Suggestion Program, and the last is visualize Implementation Plan by produce the board.Keywords:  Value Congruence, Performance, Start-up Company.